2021
DOI: 10.3390/antiox10091477
|View full text |Cite
|
Sign up to set email alerts
|

Polydatin Counteracts 5-Fluorouracil Resistance by Enhancing Apoptosis via Calcium Influx in Colon Cancer

Abstract: Colon cancer is a disease with a high prevalence rate worldwide, and for its treatment, a 5-fluorouracil (5-FU)-based chemotherapeutic strategy is generally used. However, conventional anticancer agents have some limitations, including the development of drug resistance. Therefore, there has recently been a demand for the improvement of antitumor agents using natural products with low side effects and high efficacy. Polydatin is a natural active compound extracted from an annual plant, and widely known for its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Calcium is a second messenger in many pathways related to cell proliferation and death [ 40 ]. Previous studies showed that many natural components induce anticancer properties through Ca-mediated pathways [ 41 , 42 , 43 ]. Also, magnesium plays a vital role in many physiological activities and promotes an anti-tumor activity by inducing apoptosis, autophagy, and cell cycle arrest [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Calcium is a second messenger in many pathways related to cell proliferation and death [ 40 ]. Previous studies showed that many natural components induce anticancer properties through Ca-mediated pathways [ 41 , 42 , 43 ]. Also, magnesium plays a vital role in many physiological activities and promotes an anti-tumor activity by inducing apoptosis, autophagy, and cell cycle arrest [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The spheroid morphology was detected using a DM3000 microscope (Leica Microsystems GmbH, Wetzlar, Germany). Whole images of each spheroid were transferred to ImageJ (NIH, Bethesda, MD, USA), and the total area of PC cell aggregation was quantified as previously described [ 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…Spheroid morphology was assessed using a DM3000 microscope (Leica Microsystems GmbH, Wetzlar, Germany). The total area and density of cell aggregation were calculated as described [ 23 ].…”
Section: Methodsmentioning
confidence: 99%